Geochemical study of ultramafic rocks from Latowu area of North Kolaka, Southeast Sulawesi and its implication for CO2 sequestration - S Sufriadin; Sri Widodo; Akane Ito; Tsubasa Otake; Kenzo Sanematsu (Brawijaya University, 2018)
Geochemistry of ultramafic rocks in the Latowu Area of North Kolaka Regency, Southeast Sulawesi has been investigated with the aim at deciphering of mineral characteristics, chemical composition and their potential use as carbon dioxide storage. Mineralogy was characterized by both scanning electron microscopy (SEM) and X-ray diffractometry (XRD); whereas bulk rock and mineral chemistry were analyzed by means of X-ray fluorescence spectrometry (XRF) and Electron probe microanalyzer (EPMA) respectively. Results of analyses show that lizardite is predominant serpentine mineral present, followed by chrysotile and trace amount of magnetite. Remnants of olivine and pyroxene were detected in some samples but they have been pseudomorphicly replaced by serpentine. Serpentinization of Latowu ultramafic rocks has led to decrease in grain size and density. Lizardite is characterized by fine grained particles with higher in iron. The higher Mg and Fe of the rocks indicate a suitability as feed materials for carbon dioxide sequestration. Mineral and chemical properties of ultramafic rocks have significant role in evaluating the feasibility of mineral carbonation.